Gender Bias in Advertising: A Linguistic Analysis and the Representation of Female and Male Roles - Yusri, Yusri (HUMAN: South Asian Journal of Social Studies, 2025)
Abstract. This study examines the presence and linguistic construction of gender bias in Indonesian advertisements, with a focus on the representation of female and male roles. Using a discourse analysis approach, 50 advertisements identified as containing gender-biased content were systematically examined. The analysis aimed to categorize and interpret the linguistic and visual features that contribute to gender stereotyping, objectification, and discriminatory language. The findings reveal four dominant categories of gender bias: (1) gender role stereotyping, (2) objectification of women, (3) undermining men who do not conform to traditional masculinity, and (4) the use of sexist phrases. Among these, objectification of women was the most prevalent, with nearly half of the advertisements portraying women primarily as physical objects designed to attract consumer attention. Gender role stereotyping was also prominent, reinforcing conventional and often restrictive views of masculinity and femininity. Additionally, the study highlights how men who deviate from traditional masculine norms are belittled and how sexist language is used to perpetuate harmful gender norms. The research underscores that advertisements are not neutral; instead, they function as influential social texts that reflect and shape cultural perceptions of gender. Such biased representations can reinforce societal inequalities by normalizing and legitimizing restrictive gender roles and expectations. This is particularly concerning given the influence of advertising on young and impressionable audiences. The study contributes to the growing body of literature on media representation and gender studies, highlighting the importance of linguistic scrutiny in understanding and addressing gender discrimination in mass media.Keywords: Gender Bias, Linguistics, Advertising, Language and Media